1996
DOI: 10.1038/383720a0
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus selectively blocks antigen processing and presentation of its immediate–early gene product

Abstract: Recognition of virus-infected cells by CD8+ cytotoxic T lymphocytes requires that the viral proteins be processed into peptides, the derived peptides transported into the endoplasmic reticulum and inserted into the binding groove of a major histocompatibility complex class I molecule, and the antigenic complex exported to the cell surface. However, viral pathogens can disrupt this process and interfere with immune recognition. These mechanisms may be vital to large viruses such as human cytomegalovirus (CMV), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
144
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 248 publications
(150 citation statements)
references
References 26 publications
5
144
1
Order By: Relevance
“…Prior studies have suggested that pp65 is the primary target for HCMV-specific CD8 ϩ T cell responses (10,17,18,56), and that pp65 may inhibit the processing and presentation of IE1 (57). Our data suggest that infants are capable of generating IE1-specific CD8 ϩ T cell responses, and that IE1 may be more commonly targeted by CD8 ϩ T cells.…”
Section: Discussionsupporting
confidence: 51%
“…Prior studies have suggested that pp65 is the primary target for HCMV-specific CD8 ϩ T cell responses (10,17,18,56), and that pp65 may inhibit the processing and presentation of IE1 (57). Our data suggest that infants are capable of generating IE1-specific CD8 ϩ T cell responses, and that IE1 may be more commonly targeted by CD8 ϩ T cells.…”
Section: Discussionsupporting
confidence: 51%
“…The CMV pp65-specific HLA-A2-restricted T cell clone ER1A3-3 (S. R. Riddell, unpublished data) was generated and maintained as described (17). Standard 4-h cytotoxicity assays with [ 51 Cr]sodium chromate-labeled target C1R-A2, C1R-A2-MICB, and C1R-A2-MICB-UL16 transfectants pulsed with titered concentrations of the specific pp65 NLVPMVATV peptide and the IFN-␥ and TNF-␣ release assays were carried out as described (6).…”
Section: T Cell Clones Cytotoxicity and Cytokine Release Assaysmentioning
confidence: 99%
“…C1R-MICB and C1R-MICB-UL16 cells stably transfected with a HLA-A2 cDNA construct were pulsed with titered concentrations of the CMV pp65 peptide and used as target and stimulator cells for the specific HLA-2-restricted CD8 ϩ CD28 Ϫ ␣␤ T cell clone ER 1A3-3 (Ref. 17 and S. R. Riddell, unpublished data). The results showed that under suboptimal peptide concentrations, T cell cytotoxicity declined more rapidly in the presence of UL16 (Fig.…”
Section: Effect Of Ul16 On Micb-dependent Nkg2d-mediated T Cell Activmentioning
confidence: 99%
“…To avoid immune recognition, intracellular microorganisms, including viruses [1], intracellular bacteria [2] and protozoan parasites [3][4][5][6], have evolved mechanisms which interfere with antigen presentation pathways. These mechanisms may be pivotal, especially for those pathogens causing persistent infections.…”
Section: Introductionmentioning
confidence: 99%